Microbial Treatment of Cement Kiln Dust for Utilization in Concrete - Kunal (My University, 2014)
Rapid industrialization and urbanization increases the demand of building and constructionmaterial for infrastructure development. Generation of cement kiln dust (CKD) during cementclinker manufacturing has become one of the major environmental and economical issues.Globally, cement industries generate 700 million tons of cement kiln dust every year as ameasure to control product quality and to ensure uninterrupted operation of the plant due to highalkalinity and heavy metal content, and major part of it is landfilled. In order to reduce disposalcosts utilization of CKD as construction material has become an attractive alternative to its disposal. Cement kiln dust is highly alkaline in nature which restricts its utilization in mortar and concreteas it causes crack, deformities and reduces the strength and quality of cement and concrete. Also, the alkaline leachate generated from landfilled CKD may contaminate soil, surface and ground water. So, it is necessary to monitor the alkalinity of CKD before utilization. This can be achieved by biological methods using microorganisms that requires low energy inputs, and does not produce hazardous by-products.This study presents the utilization of bacterial treated cement kiln dust in mortar and concrete, and its leachate behavior. In this study, the effect of bacterial (alkali-tolerant Bacillus strain KG1) treated cement kiln dust (after reducing the alkalinity) as partial replacement of Portlandcement (5, 10, 15, 20 and 30% w/w) on the normal consistency, setting times and hydration process of blended cement pastes, and on compressive strength at 7, 28 and 91 days of curing of blended cement mortar and concrete was investigated. Several properties such as split tensile strength, ultrasonic pulse velocity, RCPT and porosity of concrete was also studied at the age of 7, 28 and 91 days. Bacterial (isolate KG1, KG4, KG5 and KGMD1) inoculums were optimized at 0.8 O.D. for 20 days of incubation. Isolate KG1 showed maximum reduction in alkalinity and thus used for the studying the mortar and concrete properties. EDX and XRD analysis confirmed the reduction in alkalinity of powdered CKD after bacterial treatment. All the isolates were identified as member of group six (alkaliphile) of the genus Bacillus using morphological, biochemical and physiological characteristics and molecular characterization of 16S rRNA sequences. Increased water consistency, hydration and decrease in setting time was observed in 10% CKD blended cement paste, above which hydration decreases and setting time increases due to reduced alkali content in blended cement pastes. The increase in hydration at later curing ages (91 days) responsible for increase of 19.54% compressive strength in 10% bacterial treated CKD mortar compared with 0% CKD mortar. Increase of 26.6% compressive strength in 10% bacterial treated CKD concrete was observed compared with 0% CKD concrete at 91 days of curing. Similarly, increase in split tensile strength was also observed in 10% bacterial treated CKD concrete with curing age. Ultrasonic pulse velocity test results revealed that pulse velocity of concrete specimens were within the range 3500-4500 m/s and termed “good” quality of concrete. Maximum pulse velocity was observed in 10% CKD concrete specimens (both untreated and treated). The chloride permeability of concrete specimens containing untreated and bacterial treated CKD showed “very low” permeability with increasing curing period from 7 to 91 days except 20 and 30% CKD concrete which falls in low chloride permeability range. Results of water absorption and porosity showed decrease of 20% and 12.35%, respectively, in 10% bacterial treated CKD concrete compared to 10% untreated CKD concrete at 91 days of curing. Leachate analysis of fresh concrete mix showed 34-92% reduction in metal content (Ag, Cd, Cr, Cu, Fe, Mo, Ni, Pb and Zn) by different isolates. Leaching of silver (Ag) is maximally inhibited by bacterial treatment followed by Cr, Cu, Ni and Zn. It was also observed that with increasing untreated CKD in concrete the metal content increases whereas with addition of bacterial treated CKD in concrete, reduction in metal content was non- significant due to presence of metals in Portland cement. Scanning electron microscopy (SEM) results exhibits formation of non-expansive ettringite in pores and increased calcium silicate hydrate (CSH) which dense the mortar and concrete structure, and thus, increases the compressive strength in bacterial treated CKD mortar and concrete. XRD analysis confirmed the formation of CSH and non expansive ettringite within the matrix of treated mortar and concrete specimens responsible for improvement in the strength of the material.
Ph.D, BTD, Thesis
Keywords: Bacteria; cement kiln dust; concrete; mortar; biotechnology